2017
DOI: 10.1002/glia.23258
|View full text |Cite
|
Sign up to set email alerts
|

AParkinson's disease gene, DJ‐1, repairs brain injury through Sox9 stabilization and astrogliosis

Abstract: Defects in repair of damaged brain accumulate injury and contribute to slow-developing neurodegeneration. Here, we report that a deficiency of DJ-1, a Parkinson's disease (PD) gene, delays repair of brain injury due to destabilization of Sox9, a positive regulator of astrogliosis. Stereotaxic injection of ATP into the brain striatum produces similar size of acute injury in wild-type and DJ-1-knockout (KO) mice. However, recovery of the injury is delayed in KO mice, which is confirmed by 9.4T magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…The transcription factor Sox9 is expressed primarily by astrocytes and is upregulated in reactive astrocytes in models of stroke and Parkinson's disease (Choi et al, 2018;Sun et al, 2017). We tested for Sox9 expression in astrocytes adjacent to regions of ablation but found that Sox9 expression remained unchanged in all groups (Fig.…”
Section: Astrocytes Adjacent To Ablated Areas Respond With Molecular mentioning
confidence: 99%
“…The transcription factor Sox9 is expressed primarily by astrocytes and is upregulated in reactive astrocytes in models of stroke and Parkinson's disease (Choi et al, 2018;Sun et al, 2017). We tested for Sox9 expression in astrocytes adjacent to regions of ablation but found that Sox9 expression remained unchanged in all groups (Fig.…”
Section: Astrocytes Adjacent To Ablated Areas Respond With Molecular mentioning
confidence: 99%
“…Growth factors released from astrocytes including glial-derived neurotrophic factor (GDNF), brain-derived neurotrophic factor (BDNF), etc., are important for the development and survival of neurons [ 117 118 ]. Recently, we have reported that DJ-1 deficiency reduces GDNF and BDNF expression in astrocytes [ 119 ]. Several studies have reported that parkin and PINK1 are linked to the expression and/or functions of GDNF.…”
Section: Functions Of Astrocytes and Microglia Are Altered By Mutatiomentioning
confidence: 99%
“…Astrocytes proliferate and participate in repairing the damage in injured brain [ 57 122 ]. Our recent study shows that DJ-1 positively regulates astrogliosis in injured brain [ 119 ]. DJ-1 regulates astrogliosis through stabilization of Sox9 [ 119 ], a transcription factor that regulates gliogenesis during development of the brain [ 123 124 ], and astogliosis in injured brain [ 125 126 ].…”
Section: Functions Of Astrocytes and Microglia Are Altered By Mutatiomentioning
confidence: 99%
“…This included SOD1, glutathione synthetase (GSS), and dimethylarginine dimethylaminohydrolase 1 (DDAH1) of the validated myelination panel, which all function to clear damaging free radicals [59][60][61][62]. Likewise, the validated glial immunity panel included PARK7 or DJ-1, yet another mediator of oxidative stress in the brain [63,64]. Finally, highly validated markers of the vascular panel included paroxonase 1 (PON1), a lipoprotein-binding enzyme responsible for reducing oxidative stress levels in the circulation [65,66].…”
Section: Csf Biomarkers Of Brain-linked Panels Validate In a Replicatmentioning
confidence: 99%